STRATEGI PROMOSI DIGITAL DAN KUALITAS KONTEN PROMOSI DIGITAL TERHADAP MINAT CALON NASABAH (STUDY KASUS BFI FINANCE SOLO BARU) - Berlian Eva Yoruna; Desi Dwi Prasetyawati; Risma Mona Nugrahani; Santi Widyawati (Jurnal Riset Multidisiplin Edukasi, 2026)
The advancement of digital technology has transformed marketing practices within the financing industry, positioning digital media—especially social media—as the primary channel for conveying financial product information to prospective customers. This study aims to analyze the effects of digital promotion strategy and the quality of digital promotional content on the interest of prospective customers at BFI Finance Solo Baru. Employing a quantitative survey approach, data were collected from 30 purposively sampled respondents and analyzed using classical assumption tests and multiple linear regression. The results indicate that both digital promotion strategy and content quality have positive and significant effects on prospective customers’ interest, both individually and jointly. These findings underscore the importance of integrating well-designed digital promotion strategies with high-quality, informative content to enhance customer interest and improve conversion rates in financial services.